Esters as Radical Acceptors: β‐NHC‐Borylalkenyl Radicals Induce Lactonization by C−C Bond Formation/Cleavage on Esters. (4th April 2019) - Shimoi, Masaki; Maeda, Katsuhiro; Geib, Steven J.; Curran, Dennis P.; Taniguchi, Tsuyoshi
Abstract: Substituted propargyl acetates are converted into 4‐boryl‐2(5 H )‐furanones upon thermolysis in the presence of an N‐heterocyclic carbene borane (NHC‐borane) and di‐ tert ‐butyl peroxide. The acetyl methyl group is lost during the reaction as methane. Evidence suggests that the reaction proceeds by a sequence of radical events including: 1) addition of an NHC‐boryl radical to the triple bond; 2) cyclization of the resultant β‐borylalkenyl radical to the ester carbonyl group; 3) β‐scission of the so‐formed alkoxy radical to provide the 4‐boryl‐2(5 H )‐furanone and a methyl radical; and 4) hydrogen abstraction from the NHC‐borane to return the initial NHC‐boryl radical and methane. Abstract : Eine radikalische Lactonisierung von substituierten Propargylacetaten mit N‐heterocyclischen Carbenboranen wurde entwickelt. Die Reaktion erfolgt durch Cyclisierung eines β‐Borylalkenyl‐Radikals mit einem Ester mit anschließender Eliminierung einer Methylgruppe.